Clinicopathologic and radiologic features of pediatric unilateral nasal masses at a tertiary hospital - Alanazi, Eman R.; Almomen, Ali A.; Aljafer, Hadeel M.; Alazzeh, Ghaleb M.; Alkhatib, Abdurahamn M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Cases of unilateral nasal masses (UNM’s) are usually inflammatory but some are neoplastic in nature. We conducted this study to determine the clinic-pathologic features, radiological findings and patterns of UNM’s in our institution. Methods: We conducted a retroactive chart review of all pediatric cases followed and treated for medically untreatable UNM from 2015 till 2018 at King Fahad Specialist Hospital (KFSH) in Dammam, Saudi Arabia. Results: Cases of 25 patients (16 males and 9 females) with a mean age of 10.81±4.53 years were studied. There were 12 patients (48.0%) who presented with a nasal obstruction, and nasal polyp was found by fiberoptic nasal endoscopy (FNE) in 12 patients (48.0%). Two patients (8.0%) had unremarkable FNE findings. The most common site of origin of the mass was the ethmoid sinus (24.0%). Twenty patients (80.0%) had FESS, 3 (12.0%) had endoscopic excision, 1 had FESS plus abscess drainage and 1 (4.0%) had marsupialization. Two patients (8.0%) had recurrence 12 months after surgery, and one patient (4.0%) had recurrence six months after surgery. Six patients (24.0%) had malignant tumor of which 3 patients (12.0%) expired from the disease. Conclusions: Pediatric patients with a UNM may present with varied symptoms and may show unremarkable results with nasal endoscopy. However the risk of having an underlying malignant process is very high, thus a histopathologic diagnosis is warranted to confirm the diagnosis.